Using the kriging method to establish a spatially reliable interpolator for peat depth variability - M Edi Armanto; Mohd Zuhdi; D Setiabudidaya; Ngudiantoro Ngudiantoro; Elisa Wildayana (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2025)
Peatlands (according to the Governmental Regulation nr 71/2014) can be utilized for agriculture and plantation if the peat depths are less than 3 m or more than 3 m, peatlands have to be conserved or restored. Determining peat depths can be conducted in the fields by intensive surveys which were so expensive, inefficient, and ineffective, therefore it was essential to find our simple alternative methods how to measure peat depths easily. The research aimed to establish a spatially reliable interpolator for peat depth variability by utilizing the kriging method. The research was conducted in Seponjen Village, Kumpeh, Muaro Jambi, Jambi Indonesia. Primary data were processed by applying ArcGIS 10.3 software. The interpolated dataset of peat depths validated their actual dataset and performed an excellent relationship (indicated by a positive correlation coefficient, r = 0.920) and a coefficient of determination (R2 = 0.847). It indicated that the interpolated dataset could be utilized to make maps by kriging. The very deep peat (Site A) and the deep peat (Site B) showed a tendency for a strong autocorrelation of the data distribution of peat depths. Autocorrelation tended to be anisotropic towards the river on the shallow peat (Site C). A good interpolator of peat depth variability can be generated using the kriging method.